PENCEGAHAN STUNTING MELALUI EDUKASI MAKANAN BERGIZI & BERAGAM DI DESA KARANG SIDEMEN - Hayati Hayati; Achmad Wisnu Adi Riyanto; Zamrutin Fata; Ahmad Doni (Jurnal Abdi Insani, 2023)
Stunting is a serious threat for children, because it is affected thinking skill and ability to catching up on lesson. One of the causes of stunting is low nutritional intake for toddlers, pregnant women and low public awareness of the importance of a diverse and nutritious diet. The aim of implementing this community service activity is to increase the knowledge of mothers who have toddlers with indications of stunting about stunting, the causes and effects of stunting, as well as prevention of stunting through extension activities, education on local food processing to meet various needs for additional food, nutritious and balanced for pregnant women and toddlers. Extension activities are carried out using a group approach in the form of meetings, training and demonstrations, as well as an individual approach, namely visits to target homes with stunted children. The implementation of a series of extension activities went well, the target was very enthusiastic, participated actively during the process and good cooperation was established between members of the community service team with the target. Extension using a combination of group approach methods, namely extension at posyandu followed by individual/door to door visits gave effective results. In the individual approach, the delivery of counseling materials directly or face to face, is also carried out by providing healthy additional food such as milk, healthy biscuits, healthy snacks and accompaniment in consuming them. The training for posyandu cadres on processing local food into healthy snacks, how to measure height, use growth mats, and weighing toddlers by presenting competent resource persons has been very good and participatory. An increase in target knowledge regarding stunting, its causes, impacts, and prevention has been achieved, as well as an increase in the ability of posyandu cadres to measure weight and height.